Changes in the morphology traits, anatomical structure of the leaves and transcriptome in Lycium barbarum L. under salt stress - Yao, Xiao-Cui; Meng, Li-Fang; Zhao, Wang-Li; Mao, Gui-Lian (Frontiers in Plant Science, 2023)
To further elucidate the mechanism of tolerance to salinity in Lycium barbarum L.. The changes of anatomical structure, morphological, transcriptome and molecular mechanisms of Lycium barbarumm L. leaves in responses to salt stress were investigated in this study. Lycium barbarum L. exposed to 100 mmol·L-1 and 200 mmol·L-1 of salt for 7 days significantly increased the leaf thickness, along with alteration the anatomical structures. Transcriptomic analysis of the leaves identified a total of 3572 differently expressed genes (DEGs). Moreover, the functions of DEGs were further analyzed by Gene Ontology (GO) analysis and the KEGG database. There were 92 out of these genes concentrated on cell wall synthesis or modification. Meanwhile, six of DEGs were involved in cell wall loosening proteins, among which the expansin-like A2 (EXLA2) gene was up-regulated and the others were down-regulated. There was a significantly positive correlation was found between the expression of EXLA2 gene and the thickness of palisade tissue, suggesting that salt stresses induced the express of EXLA2 gene, which increased the thickness of Lycium barbarum L. leaves by promoting the longitudinal expansion of cells of palisade tissue. These results will add our knowledge to further investigate underlying molecular mechanisms of leaf thickening in Lycium barbarum L. in response to salt stresses.